Sleep quality of college students in Fujian and its influencing factors: A cross-sectional study - Fuzhi Liu; Dandan Zhu; Lifeng Deng; Yanyan Zhao; Yangjia Chen; Zhuote Tu (PLoS ONE, 2025)
Aim This study aims to investigate college students’ sleep quality, explore the factors influencing it, and provide data support for further studies. Methods College students in Fujian Province were chosen as the study sample using snowball sampling. Data was gathered from the participants through the utilization of a self-designed personal questionnaire, the Pittsburgh Sleep Quality Index(PSQI) scale, and the Mobile Phone Addiction Index (MPAI) scale. Binary logistic regression is utilized to assess the sleep quality of college students and identify risk factors. Results A total of 971 participants were included in this study. The mean total PSQI score was 4.52 ± 3.17. There were 310 students with poor sleep quality and the detection rate was 32.0%. The multivariate logistic regression analysis showed that smoking (OR(Odds ratio):1.832(1.076,3.118)), electronic product addiction(OR:2.861(1.928,4.246)), personal history of acute illness(OR:2.328(1.671,3.244)) were identified as independent risk factors.In turn, education (OR:0.594(0.456,0,772)) and parents without sleep problems (OR:0.533(0.361,0.787)) were protective factors. Conclusion College students in Fujian have some sleep problems. We should pay attention to the relationship between smoking, electronic product addiction, personal history of acute illness and sleep quality. Health policymakers should consider these factors to improve college students’ sleep quality.